2006
DOI: 10.1029/2005jd006753
|View full text |Cite
|
Sign up to set email alerts
|

Study on acidity and acidic buffering capacity of particulate matter over Chinese eastern coastal areas in spring

Abstract: [1] The analytical results of the acidity and buffering capacity of particulate matter sampled by aircraft over Chinese eastern coastal areas in March and early April 2002 are presented. The flight region covered the coastal areas from Zhuhai, Guangdong province, to Dalian, Liaoning province, and the northeastern coastal areas around Dalian, Liaoning province, with the later being the key flight areas. The results show that total suspended particles (TSP) generally appear to be acidic, having no buffering capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Both the global and regional aspects of the long-range transport of pollutants are very important, and several cooperative international experiments have thus been conducted in the western Pacific region (Huebert et al, 2003;Parrish et al, 2004;Nakajima et al, 2007). The current authors have also reported the results of aerial observations of atmospheric pollutants in a source region in China (Hatakeyama et al, 2005;Wang et al, 2006;Wang et al, 2007;Wang et al, 2008), and a receptor region (Hatakeyama et al, 1995a, b;Hatakeyama et al, 1997;Hatakeyama et al, 2004). Transformation of pollutants during their long-range transport is an important problem from the perspective of regional air quality and acid rain.…”
Section: Anthropogenic Emissions Have Been Increasing In Eastmentioning
confidence: 49%
“…Both the global and regional aspects of the long-range transport of pollutants are very important, and several cooperative international experiments have thus been conducted in the western Pacific region (Huebert et al, 2003;Parrish et al, 2004;Nakajima et al, 2007). The current authors have also reported the results of aerial observations of atmospheric pollutants in a source region in China (Hatakeyama et al, 2005;Wang et al, 2006;Wang et al, 2007;Wang et al, 2008), and a receptor region (Hatakeyama et al, 1995a, b;Hatakeyama et al, 1997;Hatakeyama et al, 2004). Transformation of pollutants during their long-range transport is an important problem from the perspective of regional air quality and acid rain.…”
Section: Anthropogenic Emissions Have Been Increasing In Eastmentioning
confidence: 49%
“…We also compared the acid neutralization states in this study with those in a previous study [ Wang et al , 2008], and found that in spring the pH of cloud water at Mount Heng was basically the same as that at a high‐elevation site, Mount Tai in North China (pH 3.80 versus 3.81), whereas the acidity of precipitation at Mount Heng was much higher that that at Mount Tai (pH 4.35 versus 4.68). The more acidic rainfall in the south could be explained by the fact that particulate matter over the southern areas has much weaker acidic buffering capacity compared with the northern areas [e.g., Wang and Wang , 1996; W. Wang et al , 2006].…”
Section: Resultsmentioning
confidence: 99%
“…Fine particulate matter, much of which can be acidic (Lawal et al, 2018;Silvern et al, 2017;Song et al, 2018Song et al, , 2019Weber et al, 2016), is also associated with harmful effects on human health. Particulate matter can also have negative environmental effects, such as reduced visibility and damage to ecological systems and historical monuments (Bouwman et al, 2002;Cheng et al, 2011;Huo et al, 2012;Ren et al, 2011;Tang et al, 2010;W. Wang, Liu, et al, 2006).…”
Section: Introductionmentioning
confidence: 99%